Gestão da informação no processo de contratação de bens e serviços na Universidade Estadual da Paraíba - Nóbrega, Angélica de Lucena (2019)
The study aimed to analyze the information management in the process of acquisition of goods and services in a state public institution of higher education. In times of valorization and strategic use of information for the improvement of organizational processes, the research proposed the identification of the information flow in the sectors involved in the process of goods and services acquisition, the description of the informational flows of each subprocess, the verification of efficiency. and possible existing information bottlenecks and formulation of an Intervention Proposal to implement changes that allow the hiring process to be optimized. The research has a practical purpose, is descriptive and presents characteristics of a case study. Data collection was performed through the request of institutional reports, research in digital files and interviews with servers that work directly with the process. The content analysis technique and data categorization were used to achieve the research objectives. The results show that information management improves communication among institutional sectors, provides more reliable information, helps to create more efficient systems, collaborates with public transparency and is able to optimize the operationalization of the process of public contracting.